Development of mathematical mindset scale for mathematics education students - Megawanti, Priarti; Supriyati, Yetti; Tjalla, Awaluddin (Institute of Advanced Engineering and Science, 2024)
Mathematical mindset is a vital element of one’s ability to understand mathematics. Teachers’ mindsets affect the way they deliver mathematics to their students, which in turn, will affect students’ mathematical mindsets. This paper discusses and proposes a mathematical mindset scale (MMS) for mathematics education students as prospective teachers. The instrument was developed to examine respondents’ mindset towards mathematics. There are three-stage processes to finalize the items in the instrument. The first stage is theory collection and preparation of instrument items based on the dimensions of challenge, resilience, effort, learning from critics, and learning from mistakes. The second stage is content validation by a team of experts. The final stage is item selection using confirmatory factor analysis (CFA). The CFA results with a total of 259 mathematics education students produced 11 questions with factor loadings above 0.5. Meanwhile, construct reliability (CR) and average variance extracted (AVE) values are all above the criterion values. The limitations of this research are also discussed further.